Low-cost and high-efficiency automated tensiometer for real-time irrigation monitoring - Arthur C. Sanches; Christopher de O. Alves; Fernanda L. F. de Jesus; Fagner L. Theodoro; Thiago A. C. da Cruz; Eder P. Gomes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Knowing the soil moisture available to plants is important for adequate management of water use in agricultural farms, with automated methods being the most accurate. However, acquisition costs are high and most of the commercially available irrigation controllers still work using pre-set times. This study aimed to develop and calibrate a low-cost automated tensiometer with high efficiency in irrigation control, based on real-time monitoring. The research was conducted at the Laboratories of Hydraulics and of Water Soil Plant and Atmosphere Relationship, which belong to the Federal University of Grande Dourados (UFGD), in Dourados, MS, Brazil, with soil classified as an Oxisol. Pressure transducers and a microcontroller were used to assimilate the pressure inside tensiometers and transform it into readings of soil water matric potential (Ψm). Thus, the calibration was carried out by comparing the different readings of the transducer and digital tension meter. Different tensions were applied to obtain a soil moisture curve, starting from the most humid point (saturated) to the driest one (oven-dried soil), collecting 20 valid points. Subsequently, the data were subjected to the normality test, with subsequent statistical analysis and regression curve models. Linear adjustments with a high coefficient of determination (R2 = 0.99) were observed, with the automated system built in this study being capable of monitoring soil water tension in real-time.